CD Review: Tour de Force - Golden, Diana (International Journal of Bahamian Studies, 2016)
Review of Tour de Force, the third album from C Force, an ensemble comprised of flutist Christine Gangelhoff, euphoniumist Christian Justilien, and pianist Christy Lee. With repertoire spanning over two centuries, the trio embarks on a musical tour to Guadaloupe, Jamaica, and Haiti on Disc One, and then Trinidad and Tobago, Curaçao, the U.S. Virgin Islands and the Bahamas on Disc Two. Just as the eclectic album artwork by John Cox might suggest, Tour de Force provides listeners with a sense of the rich tapestry of musical connections shared in art music across the Caribbean. This two-disc set (released March 2016) was recorded at the Performing Arts Center of The College of The Bahamas and produced by Terry Manning of Lucky Seven Records.